Ambient urea synthesis via electrocatalytic C–N coupling - Chen, Chen (Materials Today Catalysis, 2025)
The construction of C–N bond and synthesis of N-containing compounds directly from N2 is an extremely attractive subject. The co-electrolysis system coupled with renewable electricity provides one of the potential options for the green and controllable C–N bond construction under ambient conditions, bypassing the intermediate process of ammonia synthesis. In this review, we have summarized the recent progress in ambient urea synthesis via electrocatalytic C–N coupling from CO2 and nitrogenous species. The reaction mechanisms studies of N2 and CO2 coupling has been mainly highlighted, and the coupling enhancement strategies are emphasized for the coupling of nitrate and CO2, including intermediate adsorption regulation, functional synergy, site reconstitution and local-environment construction. Moreover, promising directions and remaining challenges are outlined, encompassing the mechanism study combining theory and experiment, reactant source and product application, optimization of urea synthesis evaluation system and the development of devices aiming to coupling system. This review aims to guide further advancements in electrocatalytic C–N coupling, facilitating the efficient and sustainable synthesis of urea for a broad spectrum of applications.